PENEGAKAN HUKUM TERHADAP PUNGUTAN LIAR PADA PENGUJIAN KENDARAAN BERMOTOR (PKB) DI DINAS PERHUBUNGAN KABUPATEN AGAM OLEH SATUAN TUGAS SAPU BERSIH PUNGUTAN LIAR - Sudarman, Sudarman (Universitas Ekasakti, 2018)
All forms of unofficial levies that have no legal basis, such levies are named as illegal fees as stipulated in Presidential Regulation No. 87 of 2016. Illegal charges as a form of extortion crime should be prevented and eradicated because it has damaged the joints of life in society, nation and The eradication of illegal levies should be done in an integrated manner by involving Saber Pungli Task Force so as to manifest law enforcement against the perpetrator by giving severe sanction to cause deterrent effect. In practice, law enforcement against perpetrators is still not optimal because it still faces obstacles as happened in Agam District Transportation Department